PHYSICOMATHEMATICAL MODEL OF CALCULATING CONTINUOUS BEAMS WITH ELASTIC YIELDING SUPPORTS - Akhmediyev, S. K.; Khabidolda, O.; Vatin, N. I.; Muratkhan, R.; Kutimov, K. S. (Journal of Mathematics, Mechanics and Computer Science, 2022)
In this work there has been studied the rod system operation dependence on the action of external force eﬀects. The system presents a multi-span continuous beam with elastic yielding supports. To identify the stress-strain state of the object under study, a precise analytical method of forces is used. The method of ﬁve moments is used as the resolving (canonical) equations. The ﬁnal results are the parameters of the stress-strain state for a ﬁve-span continuous beam with variable compliance coeﬃcients on 5 intermediate supports and an absolutely rigid left extreme support, deﬂections, bending moments, shear forces, and support reactions.Theoretical provisions and practical results can be used in the design of load-bearing beam structures in buildings and various engineering structures.